ESTIMATION OF VERTICAL DUST EMISSION FLUX AT A SITE IN THE MONGOLIAN GOBI DURING A DUST STORM PERIOD - D, Jugder (Proceedings of the Mongolian Academy of Sciences, 2018)
A meteorological and dust monitoring tower with 20 m height set up at a Nomgon site in Umnugobi Aimag in the Mongolian Gobi in 2010. The Nomgon monitoring tower equipped with wind speed sensors at 2, 4, 10 and 20 m height above the ground level (AGL), a wind direction sensor at 10 m height, a sonic anemometer to measure turbulent momentum flux at 8 m height and a soil moisture sensor at 5 cm depth. We had a purpose to measure dust concentration of PM10 at two levels using Dust-Trak instruments during an intensive observation period (IOP) of a dust event in spring. A dust storm was expected in the Mongolian Gobi from 30 April to 1 May 2016 and two Dust-Traks were set at 0.9 and 2.95 m heights in the tower during this IOP for measuring PM10. Wind data at 2 and 10 m height, three wind components at 8 m height by a sonic anemometer, soil moisture (volumetric water content) data in 5 cm depth and dust concentrations of PM10 at two levels are used in this study. These data from the sensors and instruments in the tower were used for estimation friction velocity and vertical dust flux at the Nomgon site. In association with a surface cyclone, its frontal system and a trough aloft, the expected dust storm occurred in the Mongolian Gobi during the IOP period. Dust concentrations of PM10 increased during the dust storm period due to raised wind speed in the dry conditions of air and soil. The present study aimed to estimate friction velocity (u*) and vertical dust flux (F) around Nomgon site in the Mongolian Gobi desert during the dust storm period. The estimation results were presented in this paper.